Indigenous Narratives As Cognitive Scaffolds: Enhancing Critical Thinking And Creativity In Globalized Learning Settings - Dani Waskita (CV. SINAR HOWUHOWU, 2025)
This study explores the pedagogical potential of indigenous narratives as cognitive scaffolds to enhance critical thinking and creativity in increasingly globalized learning environments. As education systems worldwide strive to cultivate higher-order thinking skills, the integration of culturally grounded narrative traditions offers an alternative and contextually rich pathway for cognitive development. Utilizing a mixed‐methods design, this research examines how indigenous narratives from diverse cultural communities function as conceptual frameworks that support learner reasoning, imaginative problem-solving, and reflective inquiry. Quantitative data were collected from 312 students across three countries—Indonesia, Malaysia, and New Zealand—while qualitative insights were derived from classroom observations and interviews with teachers implementing narrative-based instruction. Findings indicate that students exposed to indigenous narrative scaffolding demonstrated significantly higher levels of critical interpretation, creative ideation, and cultural empathy compared to those in conventional instruction. Moreover, the approach fostered a deeper sense of identity and belonging, enabling learners to navigate global content through locally meaningful cognitive anchors. This study contributes to global educational discourse by demonstrating that indigenous knowledge systems are not merely cultural artifacts but powerful pedagogical resources capable of enriching modern learning outcomes. Implications for curriculum design, teacher training, and culturally responsive pedagogy are also discussed.